Analysis of the Spatial Distribution of the African Crab in the City of Manaus / AM-Brazil - Guimarães de Souza, Michael; Félix de Castro, Leandro; Rebello da Cunha Albuquerque, Adoréa (Electronic Journal "Fórum Ambiental da Alta Paulista", 2022)
In 2003, the African snail was found for the first time in the city of Manaus, receiving from the Brazilian Institute of Environment and Renewable Resources the attribution of Achatina fulica, a species classified among the hundred worst invaders in the world. The present work presents the results of a study developed on the occurrence and the spatial distribution of this species in the capital of Amazonas. The methodological procedures were conducted through field collections, georeferencing and data projection on cartographic bases. As well as information on the conditions of precipitation, relative humidity and temperature, considering the influence of abiotic factors on the distribution of the species. The survey included 1,855 individuals, collected. The results reveal that temperature values ​​of 25 ° C accompanied by relative humidity rates of around 80% and average precipitation volumes of 17 mm bring together climatic conditions that favor the appearance of the mollusc in the city Manaus.